The Effect of Entrepreneurial Competence on Business Success through Entrepreneurial Motivation as an Intervening Variable - Destiana, Destiana; Yandes, Jufri; Santosa, Agus; Fadillah, Syarif (Jurnal Manajemen, 2023)
MSME actors need to pay attention to internal factors, namely entrepreneurial competence and entrepreneurial motivation as the strengths of MSMEs to achieve business success. The purpose of this study is to test the variable of entrepreneurial competence on business success through entrepreneurial motivation as an intervening variable to influence entrepreneurial competence on business success. The method used in this research is descriptive quantitative. Where the technique in collecting data by spreading questionnaires through google form as many as 120 respondents as culinary MSME actors in Serang Banten City. Then the collected data is processed using the SmartPLS 3.0 application. The results revealed that entrepreneurial competence, especially in indicators of having a target time, being committed to entrepreneurship, and daring to take risks has the greatest value on the entrepreneurial competency variable because it has a good impact on business success and entrepreneurial motivation. Some indicators that do not contribute to the variables of entrepreneurial motivation are indicators of family traditions and job loss. On the other hand, the variable of entrepreneurial motivation as an intervening variable between entrepreneurial competence and business success indirectly does not have a positional and significant impact on business success.